The evolution of the hypotetraploid Catolobus pendulus genome – the poorly known sister species of Capsella - Farhat, Perla; Mandáková, Terezie; Divíšek, Jan; Kudoh, Hiroshi; German, Dmitry A.; Lysak, Martin A. (Frontiers in Plant Science, 2023)
The establishment of Arabidopsis as the most important plant model has also brought other crucifer species into the spotlight of comparative research. While the genus Capsella has become a prominent crucifer model system, its closest relative has been overlooked. The unispecific genus Catolobus is native to temperate Eurasian woodlands, from eastern Europe to the Russian Far East. Here, we analyzed chromosome number, genome structure, intraspecific genetic variation, and habitat suitability of Catolobus pendulus throughout its range. Unexpectedly, all analyzed populations were hypotetraploid (2n = 30, ~330 Mb). Comparative cytogenomic analysis revealed that the Catolobus genome arose by a whole-genome duplication in a diploid genome resembling Ancestral Crucifer Karyotype (ACK, n = 8). In contrast to the much younger Capsella allotetraploid genomes, the presumably autotetraploid Catolobus genome (2n = 32) arose early after the Catolobus/Capsella divergence. Since its origin, the tetraploid Catolobus genome has undergone chromosomal rediploidization, including a reduction in chromosome number from 2n = 32 to 2n = 30. Diploidization occurred through end-to-end chromosome fusion and other chromosomal rearrangements affecting a total of six of 16 ancestral chromosomes. The hypotetraploid Catolobus cytotype expanded toward its present range, accompanied by some longitudinal genetic differentiation. The sister relationship between Catolobus and Capsella allows comparative studies of tetraploid genomes of contrasting ages and different degrees of genome diploidization.